1997
DOI: 10.1016/s0014-5793(97)01514-7
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and conformational characterisation of HSP‐3, a stallion seminal plasma protein of the cysteine‐rich secretory protein (CRISP) family

Abstract: HSP-3 is a member of the cysteine-rich secretory protein (CRISP) family from stallion seminal plasma. We report a large-scale purification protocol for native HSP-3. This protein is a non-glycosylated polypeptide chain with a pI of 8^9 and an isotope-averaged molecular mass of 24 987 þ 3 Da. The molecular mass of HSP-3, determined by equilibrium sedimentation, is 26 kDa, showing that the protein exists in solution as a monomer. The concentration of HSP-3 in the seminal plasma of different stallions ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 47 publications
0
26
1
Order By: Relevance
“…Within the Eukaryota, the majority of sequences reside within the Viridiplantae (183) and Metazoa (529), primarily distributed between Mollusca, Nematoda (109), Arthropoda (flying winged insects of the Neoptera) (216) and Chordata (170). Within the Chordata, proteins have been primarily identified from squamates (snakes and lizards) (49), primates (36), and rodents (41). The focus of the current review is the CAPs of chordate origin, especially those found within mammals.…”
Section: The Cap Superfamily Conservation and Evolutionary Distrimentioning
confidence: 99%
See 1 more Smart Citation
“…Within the Eukaryota, the majority of sequences reside within the Viridiplantae (183) and Metazoa (529), primarily distributed between Mollusca, Nematoda (109), Arthropoda (flying winged insects of the Neoptera) (216) and Chordata (170). Within the Chordata, proteins have been primarily identified from squamates (snakes and lizards) (49), primates (36), and rodents (41). The focus of the current review is the CAPs of chordate origin, especially those found within mammals.…”
Section: The Cap Superfamily Conservation and Evolutionary Distrimentioning
confidence: 99%
“…CRISP2 was originally identified in the guinea pig as auto-antigen 1 (28,29), in the mouse as TPX1 (2,30), and in the rat (31,32), human (33), and horse (34). CRISP3 was originally identified in the mouse (25), followed by the human (also called specific granule protein 28) (33,35), and the horse (also called horse seminal plasma protein-3) (34,36,37). CRISP4 has been identified only in the mouse and the rat (38,39).…”
Section: A Cysteine-rich Secretory Proteins (Crisps) Subfamilymentioning
confidence: 99%
“…Various functions have been ascribed to individual SCP/TAPS proteins, including protease (Milne et al, 2003), protease inhibitor (Yamakawa et al, 1998), signaling molecule (Olsen et al, 2001), ion channel regulator (Morrissette et al, 1995), and membrane disrupter/destabilizer (Magdaleno et al, 1997). Recently, it has been suggested that SCP/TAPS proteins are novel calcium-binding serine proteases (Milne et al, 2003), which require dimerization to form a functional active site (Serrano et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the epididymal proteins known as CRISP-1, members of the family include CRISP-2 (also called TPX-1), which is expressed in the testes of mice, humans, guinea pigs, and rats [21][22][23]; CRISP-3, which is detected in various cell types and tissues such as equine seminal vesicles [24,25], salivary glands of mice and humans [18,26], murine pre-B cells [27], and human neutrophils [28]; and two nonmammalian venom proteins, helothermine [29,30] and cysteine-rich venom protein (CRVP) [31]. As all CRISP members, DE contains 16 cysteine residues, 10 of which are clustered in the C-terminal region of the molecule, suggesting a fundamental role for these amino acids in the biological activity of the protein.…”
Section: Introductionmentioning
confidence: 99%